An Empirical Study: Influencing Factors of Normative Susceptibility, Collectivism, Novelty, Value Consciousness on Consumer’s Attitude towards Pirated Software in Bangkok, Thailand - Chaipoopirutana, Sirion (ABAC ODI JOURNAL Vision. Action. Outcome, 2019)
Abstract This study aimed to find a relationship between normative susceptibility, collectivism, novelty seeking, value consciousness, and consumers’ attitude towards pirated software. The researcher collected the data from customers who has experienced to purchase pirated software from two locations in Bangkok metropolis. The final data were 369 respondents. Non-probability was used to find sampling unit by using quota and convenience sampling. All hypotheses were tested using Structural Equation Model (SEM). The adequate quality of model was measure by measurement model in order to use discriminant validity, convergence validity, and goodness-of-fit. The results of this study, the researcher found that normative susceptibility and collectivism were significant relationship with consumers’ attitude towards pirated software. The results of novelty seeking and value consciousness were not statistical significant relationship with consumers’ attitude towards pirated software.